La ¿relativa? aplicación del principio de legalidad en Derecho Penal Internacional - Natalia Barbero (Nuevo Foro Penal, 2017)
It is assumed in this text that criminal law must adapt to the limits that derive from the Rule of Law. That is why the Rome Statute provision is imposed in which a range of sources that are notoriously strange to the Criminal Law are foreseen. Thus, despite the internationalists see the art. 21 of the Rome Statute as a limitation to the range of sources of international law, from the criminal (and the Rome Statute is criminal law) is seen as an exaggerated and risky permission of leaking from sources outside the strict punitive scope.